Effectiveness and Tolerability of Repeated Courses of Viscosupplementation in Symptomatic Hip Osteoarthritis: A Retrospective Observational Cohort Study of High Molecular Weight vs. Medium Molecular Weight Hyaluronic Acid vs. No Viscosupplementation - De Lucia, Orazio; Pierannunzii, Luca Massimo; Pregnolato, Francesca; Verduci, Elisa; Crotti, Chiara; Valcamonica, Elisabetta; Pisoni, Laura; Comi, Daniela; Lonati, Paola Adele; Meroni, Pier Luigi; Murgo, Antonella (Frontiers in Pharmacology, 2019)
Background: Nonsurgical management of symptomatic hip osteoarthritis needs real world evidence. We evaluated the effectiveness and tolerability of US-guided intra-articular treatment of two hyaluronic acids (HAs) commercially available in Italy and investigated predictors of response. Methods: outpatient records including three cohorts: 122 subjects treated with medium (1,500-3,200 kDa; Hyalubrix®) molecular weight (MW) or high (HylanG-F20; Synvisc®) MW HAs and 20 controls taking NSAIDs/analgesics on demand were retrospectively analyzed. Pain VAS score, WOMAC, NSAIDs/analgesics consumption, causes of suspension were available at 1, 6, 12 and 24 months after first administration. As selection bias usually affects observational retrospective studies, a quasi-randomization process was attained by performing propensity score approach. Results: Propensity score adjustment successfully allowed comparisons among balanced groups of treatments. VAS and WOMAC considerably decreased over time in treated groups independently of the radiological grade (p<0.001). On the other hand, the control group showed only a slight and rather uneven variation in VAS. Mean score changes were comparable in both HA cohorts from the earliest stages (VAS(HA1,500-3,200kDa)T1vsT0=-20%; VAS(HylanG-F20)T1vsT0=-23%/ WOMAC(HA1,500-3,200kDa)T1vsT0=-17%;WOMAC(HylanG-F20)T1vsT0=-19%), reaching a further substantial reduction after 12 months (VAS(HA1,500-3,200kDa)T12vsT0=-52%; VAS(HylanG-F20)T12vsT0=-53%/WOMAC(HA1,500-3,200kDa)T12vsT0=-45%; WOMAC(HylanG-F20)T12vsT0=-47%). Almost 11% (=13/122) of ineffectiveness and few moderate local side effects (3%=4/122) were detected. Conclusions: Viscosupplementation in a real-life setting seems to provide a sound alternative in pain management in comparison to oral NSAIDs/analgesics, guaranteeing a reduced intake of pain killer medications. Analgesic effectiveness, functional recovery and reduced joint stiffness, extend and improve over 12 and 24 months, suggesting that repeated administrations achieve an additive effect.